The challenge of quantifying national well-being: lessons from the Measures of Australia's Progress initiative. (1st November 2016) - Howard, Cosmo; Chambers, Amber
ABSTRACT: In recent decades, the use of gross domestic product (GDP) as a proxy for national well-being has been criticised on the grounds it excludes important social and ecological considerations. Several alternatives have been proposed that promise to generate more comprehensive and balanced quantitative measures of well-being, but all of these alternative indicators remain contested and controversial. This paper critically reviews Australia's contribution to this effort: the Australian Bureau of Statistics' (ABS's) Measures of Australia's Progress initiative. Unlike many other alternatives to GDP, the Australian initiative does not settle on one measure but uses expert-mediated public consultation to establish a 'dashboard' of indicators. In so doing, this model makes explicit the serious challenges confronting efforts to coherently define and measure progress in late modernity. In its attempt to integrate diverse views on national progress, the ABS has created an ambiguous tool that is not being taken up in public and political discourse.